Kin Signatures Learned in the Egg? Red-Backed Fairy-Wren Songs Are Similar to Their Mother's In-Nest Calls and Songs - Dowling, Jenélle L.; Colombelli-Négrel, Diane; Webster, Michael S. (Frontiers in Ecology and Evolution, 2016)
Many vocal animals recognize kin using vocal cues, in territorial contexts and in rearing young, but little is known about the developmental and evolutionary mechanisms that produce vocal kin recognition systems. In the cooperatively breeding red-backed fairy-wren (Malurus melanocephalus), females give specific “in-nest calls” while incubating their eggs. Elements from these calls are incorporated into chicks' begging calls, and appear to be used by parents for recognition. This is likely a result of an embryo's ability to learn the call elements in the egg. Here, we explore the idea that maternal vocal elements may be incorporated into offspring's adult songs, and serve as signatures of kinship, which would aid in kin recognition and benefit signaler and receiver. To investigate this hypothesis, we tested for similarities between maternal vocal elements (in-nest calls and songs) and songs of their adult offspring. We then determined whether offspring songs were more similar to the maternal vocalizations they heard only as embryos (in-nest calls), or maternal songs they heard throughout development, but mostly post-fledge (mothers' full songs). We used dynamic time warping to compare maternal vocal elements with elements in their offspring's adult songs. The elements of each offspring were more similar to the elements of their own mother than to the elements of any other female (but only for the average similarity score), suggesting they may serve as kin signatures. We also found that offspring song elements were more similar to their mother's song elements than to their mother's in-nest call elements. In addition, female in-nest call elements were more similar to their own song elements than to the song elements of any other female. Offspring that produced song elements highly similar to their mother's song elements also had song elements highly similar to their mother's in-nest call elements. Signals of kinship may function critically for survival and successful reproduction, by allowing an individual to allocate care and defense to kin and to avoid mating with genetic relatives. Understanding the processes that facilitate effective kin recognition, including development of kin signatures, helps us to understand how these crucial signaling systems may have evolved.